Biosafety, histological alterations and residue depletion of feed administered anti-parasitic drug emamectin benzoate in golden mahseer, Tor putitora (Hamilton, 1822) as a model candidate fish for sport fishery and conservation in temperate waters - Mallik, Sumanta Kumar; Singh, Shivam; Shahi, Neetu; Patil, Prasanna Kumar; Kala, Krishna; Pathak, Richa; Giri, Abhay Kumar; Das, Partha; Tandel, Ritesh Shantilal; Chandra, Suresh; Krishna, Nanitha; Ravindran, Rajisha; et al. (Frontiers in Pharmacology, 2023)
The increased prevalence of parasitic diseases has caused enormous economic and ecological threats to global aquaculture, and led to enhanced worldwide use of emamectin benzoate (EB) as an anti-parasitic agent. In the present study, the attempt has been made to study the biosafety and toxic effects of graded levels of EB on golden mahseer juveniles through an extended feeding. The graded doses of EB viz., 1× (50 μg/kg fish/day), 2× (100 μg/kg fish/day), 5× (250 μg/kg fish/day) and 10× (500 μg/kg fish/day) were administered to golden mahseer juveniles through medicated diet for 21 days at water temperature of 18.6 ºC. The higher doses of EB did not cause any mortality during and 30 days after the end of medication period, but considerable variations in feeding and behavior were observed. Severe histological alterations observed after EB-diets (5× and 10×) were vacuolation, pyknotic nuclei, melanomacrophage centre and necrosis in liver; Bowman’s capsule dilation, degenerated renal tubules in kidney; myofibril disintegration, muscle oedema, splitting of muscle fibres, migration of inflammatory cells in muscle; and abundant goblet cells, dilated lamina propria and disarrangement of mucosa in intestine tissues. The residual concentrations of EB metabolites Emamectin B1a and B1b were analyzed using muscle extracts and were found to be peaked during medication period followed by gradual depletion in post-medication period. The outcome of this study showed that the Emamectin B1a residual concentration in fish muscle in 1×, 2×, 5× and 10× EB treatment groups were 1.41+0.49, 1.2+0.7, 9.7+3.3 and 37.4+8.2 μg/kg at 30 days of post-medication period, respectively, which falls under the maximum residue limits (MRLs) of 100 μg/kg. The results support the biosafety of EB at recommended dose of 50 μg/kg fish/day for 7 days. As residue of EB is recorded falling within the MRL, no withdrawal period is recommended for golden mahseer.